Polysaccharide-based biomaterials for regenerative therapy in intervertebral disc degeneration - Xin Wang; Yixue Huang; Yilin Yang; Xin Tian; Yesheng Jin; Weimin Jiang; Hanliang He; Yong Xu; Yijie Liu (Materials Today Bio)
Intervertebral disc (IVD) degeneration represents a significant cause of chronic back pain and disability, with a substantial impact on the quality of life. Conventional therapeutic modalities frequently address the symptoms rather than the underlying etiology, underscoring the necessity for regenerative therapies that restore disc function. Polysaccharide-based materials, such as hyaluronic acid, alginate, chitosan, and chondroitin sulfate, have emerged as promising candidates for intervertebral disc degeneration (IVDD) therapy due to their biocompatibility, biodegradability, and ability to mimic the native extracellular matrix (ECM) of the nucleus pulposus (NP). These materials have demonstrated the capacity to support cell viability, facilitate matrix production, and alleviate inflammation in vitro and in vivo, thus supporting tissue regeneration and restoring disc function in comparison to conventional treatment. Furthermore, polysaccharide-based hydrogels have demonstrated the potential to deliver bioactive molecules, including growth factors, cytokines and anti-inflammatory drugs, directly to the degenerated disc environment, thereby enhancing therapeutic outcomes. Therefore, polysaccharide-based materials provide structural support and facilitate the regeneration of native tissue, representing a versatile and effective approach for the treatment of IVDD. Despite their promise, challenges such as limited long-term stability, potential immunogenicity, and the difficulty in scaling up production for clinical use remain. This review delineates the potential of various polysaccharides during the fabrication of hydrogels and scaffolds for disc regeneration, guiding and inspiring future research to focus on optimizing these materials for clinical translation for IVDD repair and regeneration.